SERAPAN UNSUR HARA FOSFOR (P) TANAMAN CABAI RAWIT (Capsicum frustescens L.) PADA APLIKASI PGPR (Plant Growth Promoting Rhizotobacter) DAN TRICHOKOMPOS.: Phosphorus (P) Nutrient Absorption of Cayenne Pepper (Capsicum frustescens L.) in PGPR (Plant Growth Promoting Rhizotobacter) Application and Trichocompost. - Lisa Lisa; Bibiana Rini Widiati; Muhanniah Muhanniah (Program Studi Agroteknologi Fakultas Pertanian, Peternakan, dan Kehutanan Universitas Muslim Maros, 2018)
The research objectives were: to determine the dose of PGPR which can increase phosphorus nutrient absorption in cayenne pepper, the dose of Trichocompos which can increase phosphorus nutrient absorption in cayenne pepper, and if there is an interaction between the administration of PGPR doses and Trichocompost doses which can increase nutrient absorption phosphorus in the growth and production of cayenne pepper plants. The experiment was conducted in experimental form using Split Plot Design (SPD) with all treatments were given Trichocompost and PGPR. The main plot of Trichocompost (t), consists of 3 levels of treatment, namely: t1: Trichokompos 225 g. hole-1 t2: Trichokompos 450 g. hole-1 t3: Trichokompos 675 g. hole-1 . The PGPR (p) sub plots consists of 4 levels, namely: p0 = without PGPR, p1 = PGPR 3 ml. water-1, p2 = PGPR 6 ml. water-1, and p3 = 9 ml PGPR. water-1. Each treatment consists of 3 repetition so the total number of plantations is 36 experimental units or beds. The results showed that: the use of PGPR with a dose of 9 ml. water-1 can increase phosphorus nutrient absorption, and concentration of PGPR 6 ml. water-1 can increase root wet weight, fruit weight, crop number, and diameter of cayenne fruit. The use of trichocompos at a dose of 450 g. hole-1 has no significant effect in increasing of phosphorus nutrient absorption in cayenne pepper plants. There is an interaction between giving 6 ml PGPR doses. water-1 and trichocompost dose 450 g. hole-1 which can increase the number of leaves, root wet weight, fruit weight, number of fruit crops, and diameter of cayenne fruit.